Potret Paradigma Pengembangan Pendidikan Islam di Indonesia - Muhaimin, Muhaimin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2001)
Islamic education in Indonesia has long been on the topic of discussion, policies for its development has also been made. However, there are some hindrances in advancing Islamic education. It deals with the unclear paradigm of Islamic education. This article is intended to clarify some platforms of lslamic education in Indonesia. It elaborates three platforms which gives us clear ideas how to develop Islamic education in Indonesia. The madrasa development policy seeks to accommodate three main interests, namely (1) as a vehicle for fostering the spirit or practice of Islamic life; (2) clarifying its orientation to strengthen the existence of madrassas as equals with the school system, as a vehicle for developing intelligent, knowledgeable, personality and productive citizens; and (3) to respond to future demands, in the sense of being able to give birth to humans who have access to the era of globalization, industrialization and the information age.